Responding to Urban Sphere’s Mobility Challenge: A Case of Nepal’s Historic City - Maki Ito Tsumagari; Bipin Ojha (Jurnal Studi Pemerintahan, 2021)
Urbanization is a globally shared challenge and Nepal, a small developing country in the foot of the Himalayas, is no exception. For Lalitpur Metropolitan City (LMC), the country’s second ranked city in terms of population density, the situation is complex as numerous historic and artistic monuments including a UNESCO World Heritage property make structural adjustment prohibitive. As a practical and sustainable response to the mobility challenge, then, LMC has teamed up with the City’s stakeholders to transform into a cyclable city. Based on a case study that employed in-depth qualitative interviewing of specialized populations, this study attempted to validate City’s course of actions in light of global trend in the use of bicycles, and discussed the movement from the perspective of sustainable urban governance. The study found that the case city is on the right trajectory for tackling urbanization challenges with sustainable means, aided by the collective wit of the political, administrative, and citizens’ power. Their effort was validated by the initiative’s alignment with the global benchmarking on the use of bicycle for sustainable mobility. The study concluded that factors such as collaborative public service design and local government led spatial management are holding keys for sustainable urban governance.